1976
DOI: 10.1038/bjc.1976.133
|View full text |Cite
|
Sign up to set email alerts
|

Association of medullary carcinoma of the thyroid with carcinoembryonic antigen

Abstract: Summary.-To investigate the association between medullary carcinoma of the thyroid (MCT) and carcinoembryonic antigen (CEA), we assayed 78 sera from patients with thyroid diseases for CEA, employing the radioimmunoassay of double antibody technique. All 13 sera from patients with MCT had high levels of CEA, ranging from 14 to 170 ng/ml. Increased serum CEA was noted .even in cases of small, localized carcinoma. By contrast, serum CEA levels were normal (below 10 ng/ml) in all other histological types of thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1
2

Year Published

1976
1976
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(37 citation statements)
references
References 10 publications
2
32
1
2
Order By: Relevance
“…Quite recently we have demonstrated that carcinoembryonic antigen (CEA), a tumor-associated fetal antigen described by Gold and Freedman (1965), is markedly increased in sera and tissues of the MCT in contrast with other types of thyroid carcinomas (Ishikawa and Hamada, 1976). The results obtained prompted us to investigate the relationship between CEA levels and cellular activity of the tumor, making comparison with the CT secretion.…”
Section: Synopsismentioning
confidence: 95%
See 1 more Smart Citation
“…Quite recently we have demonstrated that carcinoembryonic antigen (CEA), a tumor-associated fetal antigen described by Gold and Freedman (1965), is markedly increased in sera and tissues of the MCT in contrast with other types of thyroid carcinomas (Ishikawa and Hamada, 1976). The results obtained prompted us to investigate the relationship between CEA levels and cellular activity of the tumor, making comparison with the CT secretion.…”
Section: Synopsismentioning
confidence: 95%
“…Positive CEA find-ings were also very high, though slightly lower compared with CT, and further, the levels in excess of 40ng/ml ("diagnostic levels") were shown in 86.7%. Because elevated levels of CEA are rarely seen in other thyroid diseases (Ishikawa and Hamada, 1976), CEA assay appears very useful for diagnosis of the MCT.…”
Section: Synopsismentioning
confidence: 99%
“…Because an MTC tumor expresses and secretes carcinoembryonic antigen (CEA), it constitutes a potential application for radioimmunotherapy with anti-CEA antibodies (13). Our group demonstrated the efficacy of radioimmunotherapy in the treatment of MTC in animal model or in phase I/ II clinical trials (14)(15)(16)(17).…”
mentioning
confidence: 98%
“…Because MTC expresses and secretes carcinoembryonic antigen (CEA), it constitutes a potential application for RIT with anti-CEA antibodies. 13 Our group demonstrated the efficacy of RIT in the treatment of MTC in animal models and in phase 1 and 2 clinical trials. [14][15][16][17] Nevertheless, RIT efficacy must be improved, in particular, in cases of aggressive forms or large tumor masses.…”
mentioning
confidence: 99%